(untitled) (Veterinary Science, 2021)
The bush fox (Cerdocyon thous) is a wild canid that is present in the province of Misiones. Like many other species in the order of the carnivores, foxes are susceptible to the Canine Distemper Virus (CDV). The objective of this work is to communicate and describe the first CDV case in a free-living bush fox (C. thous), found in a peri-urban area of the city of Puerto Iguazú.